Current Special Laws in Taiwan as an Impediment to the Development of Relations with the People’s Republic of China - Xianyi, Zeng; Ding, Zheng (Columbia Journal of Asian Law, 1989)
Those in the international community who are interested in China realize that the issue of Taiwan is a very important and extremely sensitive part of China’s affairs. In 1949, the Guomindang (KMT) retreated to Taiwan, and the People’s Republic was established under the leadership of the Communist Party of China. In the four decades since then, the nation has been divided for political reasons. During the last forty years, the KMT and the Communist Party have each overcome difficulties and setbacks and have realized great achievements. Recently, following the trend toward relaxation of international tensions, both sides have taken steps to mitigate hostility and to improve relations. However, sixty years of conflict stand between the KMT and the Communist Party, exposing a confrontation of ideology and different political and legal systems, economic structures, and life styles. There is still a long way to go to further improve relations and eventually to unify the nation.